A review of port devolution and governance models with compound eyes approach. Issue 4 (4th July 2017) - Lee, Paul Tae-Woo; Lam, Jasmine Siu Lee
ABSTRACT: Port devolution and port governance are focal issues in port studies. This paper argues that the previous typology of port devolution and port governance, including port function matrix models, might have to be modified, in particular for Asian port cases, because they have not considered socio, economic, and political systems and historical aspects behind the port devolution continuum. This paper uses the "compound eyes" approach comprising of many similar, closely-packed facets called ommatidia, with a multiple angle view, to revisit and review previous port devolution and governance models. The paper aims to identify the limitations and rectify fallacies in previous port studies by conducting a critical review and taking a couple of Asian container port cases as examples. This paper contributes to the literature of port devolution and governance, illuminating crucial gaps that the previous studies have not addressed.